Earthquake Hazard Analysis in Probolinggo Region as a Mitigation Effort Using Probabilistic Seismic Hazard Analysis Method: Analisis Bahaya Gempa Bumi Di Wilayah Probolinggo Sebagai Upaya Mitigasi Menggunakan Metode Probabilistic Seismic Hazard Analysis - Al Ghifari, Muhammad Taufiq Akbar; Sunardi, Bambang; Susanti, Dwi Budi; Handayani, Wuri (Prodi Fisika Fakultas Sains dan Teknologi UIN Sunan Kalijaga Yogyakarta, 2024)
Probolinggo is one of the areas traversed by an active fault, namely the Probolinggo Fault. As an area that is prone to earthquake disasters, Probolinggo needs to have an earthquake hazard modeling as a mitigation effort to minimize the impact of an earthquake that occurs in the future. Earthquake hazard modeling is a multidisciplinary science that aims to predict earthquakes, and the ground shaking they produce. One method that can be used is Probabilistic Seismic Hazard Analysis (PSHA). This study aims to analyze the earthquake hazard in Probolinggo area using the PSHA method as an effort to mitigate earthquake prone areas. The data used is historical earthquake data from the Agency for Meteorology, Climatology, and Geophysics (BMKG) for the 1973-2020 period with a magnitude of Mw ≥ 5, a depth of 0-300 km, and a radius of 300 km from the study area. The earthquake source model used includes megathrust, faults, and background earthquake sources. Three sets of Ground Motion Prediction Equation (GMPE) were used for each earthquake source. PSHA was performed for the condition of a 2% probability of being exceeded in 50 years. The average shear wave velocity to a depth of 30 m (Vs30) from the United States Geological Survey (USGS) were used to model the peak ground acceleration on the surface. The results showed that the peak ground acceleration (PGA) at bedrock ranged from 0.27 to 0.71 g. PGA at the surface (PGAM) ranges from 0.27 to 0.83 g. The distribution of the amplification value in Probolinggo area is 1.02 to 1.12. The earthquake hazard analysis obtained shows that the northern part of the Probolinggo area has a higher earthquake hazard than the southern part. The results of the study can be used as consideration in regional development based on earthquake risk reduction.